Propulsive Efficiency of Rowing - Kleshnev, V. (coachesinfo.com)
The values of propulsive rowing efficiency found in this study were slightly higher than the data in previous research. Future experiments which include determination of the drag and lift components of the blade force would provide more accurate results. The presented rowing efficiency data allowed us to produce the following recommendations for practitioners: Improvement of blade efficiency could give much higher effect on rowing performance (3-5%) than improvement of boat velocity efficiency (0.5-0.8%). Dependencies of these two components of efficiency on stroke rate and boat velocity produce conflicting requirements: blade efficiency increases with rowing intensity, but boat efficiency is reduced at the same time. Average force and especially increasing the ratio of average to maximal forces are essential for increasing of blade efficiency. Rapid force development at the catch and longer maintenance at finish of the drive must be emphasised instead of applying highest peak force in the middle of the drive. More attention should be paid to the shortening of the Drive Time, especially at high stroke rates. The figures of drag coefficient derived in the study could be used for the approximate calculation of rowing power for achieving of a target boat velocity in each boat type.